Penerapan Algoritma Convolutional Neural Network Arsitektur ResNet-50 untuk Klasifikasi Citra Daging Sapi dan Babi - Dodi Efendi; Jasril Jasril; Suwanto Sanjaya; Fadhilah Syafria; Elvia Budianita (JURIKOM (Jurnal Riset Komputer), 2022)
Meat is one of the food ingredients needed by humans. The price of pork is cheaper than beef, which has led to the practice of mixing beef with pork for the purpose of making big profits. In plain view, the difference between beef and pork is not striking, so it is difficult for ordinary people to distinguish between them. In terms of color, pork is paler than beef. In terms of texture, beef is stiffer and tougher than pork. In terms of fiber, beef is clearer than pork, so we need a system that can identify the two types of meat. This study uses the Convolutional Neural Network (CNN) algorithm with the ResNet-50 architecture with 3 types of optimizers such as Stochastic Gradient Descent (SGD), Adam, and RMSprop. The dataset used for training first goes through 2 stages of preprocessing, namely cropping and resizing. The results of the study show that the SGD optimizer can outperform the Adam and RMSprop optimizers with 97.83% accuracy, 97% precision, 97% recall, and 97% f1 score with batch size 32, learning rate 0.01, and epoch 50.